Mathematical modelling and experimental investigation of the hybrid desiccant cooling system - Patanwar P.; Shukla S.K. (My University, 2025)
In this paper, an experimental study has been conducted on the hybrid desiccant cooling system by removing the latent heat and sensible heat of air separately by mixing it with the desiccant solution in a counter flow manner. This makes air totally dry and thus saves the energy to cool the air in the refrigeration system. The desiccant chosen here is the aqueous solution of calcium chloride. The packed bed inside the absorber as well as the regenerator consists of a polypropylene cascade ring for the efficient mixing of air and desiccant solution. The effects of various parameters such as desiccant inlet temperature, air inlet temperature, mass flow rate of air and desiccant solution have been studied to investigate the performance of the system. Comparing the results with previous studies, a fair agreement has been reported. © 2012 © 2012 Taylor & Francis.